Mobile Application for Teleorientation and Telemonitoring in the care of COVID 19: User Evaluation: Telemonitoramento no cuidado da COVID 19 - CAVALCANTE FILHO, JOAO BATISTA; Triarca, Patrick Joaner Lobo; De Paula, Luciana Guiamarães Nunes; Godoy, Flavia Giovannone de; Santos, Maria Heliziane dos (Journal of Health Care, 2022)
Introduction: This study is the result of the Extension Project Monitora COVID 19 - developed by the Federal University of Sergipe - which aims to include, under the guidance of professors at the institution, graduate students in teleorientation and telemonitoring carried out through an application created for this purpose - Application Monitora COVID 19. Objective: To assess the satisfaction of users of Application Monitora COVID 19 residing in the state of Sergipe - Brazil. Materials and Methods: This is a descriptive, cross-sectional study, through closed questions in a questionnaire produced by the researchers and sent to users of the application electronically. Results: it was observed that 57.32% of users said they were very satisfied with the use of the application, while 9 users (5.73%) said they were very dissatisfied with its use. When analyzing the question that used the Net Promoter Score (NPS) methodology, a total of 75.80% of users were classified as promoters and 9.55% as detractors, resulting in an NPS of 66.25, considered very good. Conclusion: The COVID 19 pandemic increased the possibilities of using Information and Communication Technologies to expand access to health care. In this experience, the use of an application for teleorientation and telemonitoring was well evaluated by users and may be a legacy of the strategies for coping with the pandemic.
Keywords: COVID 19 Pandemic; Telemedicine; Telemonitoring; Teleorientation; Information Tecnology; Consumer Behavior.